Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Standar Akuntansi Pemerintah, dan Penerapan Sistem Akuntansi Keuangan Daerah Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Lumajang (Studi Kasus pada Kantor BPKD Kabupaten Lumajang) - Uswatun Hasanah Mufahharoh; Moh. Amin; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of human resource competence, the application of government accounting standards, and the application of regional financial accounting systems on the quality of local government financial reports in Lumajang Regency. The number of samples used in this study were 45 respondents with a purposive sampling method. Data collection was carried out by distributing questionnaires to all BPKD employees in Lumajang Regency and processed using SPSS Statistics 24.0. The results of this study indicate that the competence of human resources and the implementation of the regional financial accounting system have no effect on the quality of the financial reports of the regional government of Lumajang Regency. While the application of government accounting standards has a positive effect on the quality of the financial reports of the regional government of Lumajang district.Keywords: Competence of human resources, government accounting standards, regional financial accounting systems, and quality of regional financial reports